Aggregation of erythrocytes: a novel activity of HBD-2 - Semeniuk, D.O.; Starenka, I.O.; Pogribna, A.P.; Sokol, I.V.; Govsieiev, D.O. (Вiopolymers and Cell, 2019)
Aim. To investigate an ability of HBD-2 to induce aggregation of erythrocytes. Methods. Aggregation assay, turbidimetry, light microscopy. Results. We have identified aggregation of erythrocytes in presence of at least 12.5 μM of HBD-2 that was confirmed by light microscopy. Effect was depended on HBD-2 concentration and diminished in presence of NaCl. Conclusions. HBD-2 can induce salt-sensitive aggregation of erythrocytes in dose-dependent manner. Мета. Дослідити здатність HBD-2 індукувати агрегацію еритроцитів. Методи. Агрегаційний тест, турбідиметрія, світлова мікроскопія. Результати. Було виявлено агрегацію еритроцитів в присутності щонайменше 12,5 μМ HBD-2, що було підтверджено мікроскопічним дослідженням. Ефект залежав від концентрації HBD-2 та пригнічувався за присутності NaCl. Висновки. HBD-2 здатен індукувати соле-чутливу агрегацію еритроцитів дозо-залежним чином. Цель. Исследовать способность HBD-2 индуцировать агрегацию эритроцитов. Методы. Агрегационный тест, турбидиметрия, световая микроскопия. Результаты. Было выявлено агрегацию эритроцитов в присутствии не меньше 12,5 μМ HBD-2, что было подтверждено микроскопическим исследованием. Эффект зависел от концентрации HBD-2 и угнетался в присутствии NaCl. Выводы. HBD-2 способен индуцировать соле-чувствительную агрегацию эритроцитов дозо-зависимым образом.